EVALUATION OF THE IN VIVO AND IN VITRO ANTIDIARRHEAL EFFECTS OF METHANOL LEAF EXTRACTS OF Boscia salicifolia IN MICE AND ISOLATED RABBIT JEJUNUM - admin, MAILAFIYA M; ELON R. I; JOHNNY. J; ATINGA V. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Diarrhoea is one of the leading causes of preventable death in developing countries and mainly affects children and infants. The leaves of Boscia salicifolia has been used as an herbal remedy in the treatment of diarrhea in many parts of Northern Nigeria and West Africa. Thus, this study was aimed at investigating this enthnomedical claims of the plant extract on the gastrointestinal tracts. The fresh leaves were collected from Kalshingi town of Akko Local Government area Gombe State in August. They were dried for a week under the sun and the grounded into powder. Six hundred (600 g) grams of the powdered leaves were subjected to successive cold extraction with 80 % methanol. The extract was used for acute toxicity, phytochemical screening, antidiarrheal and spasmolytic evaluation of acetylcholine, histamine and serotonin induced contractions on rabbit jejunum. The preliminary phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, terpenes, steroid and glycosides. The effect methanol leaf extract of B. salicifolia on castor oil-induced diarrhoea in mice showed a significant reduction (p<0.05) in the diarrheal drops with increase percentage inhibition of diarrhea 45.95, 40.54, and 29.72% at 380, 760, and 1140 mg/kg doses of the extract, respectively. The standard drug (loperamide 5 mg/kg) inhibited diarrhoeal droppings by 51 %. The extract significantly (p<0.001) decreases the force of rabbit ileum contraction induced by acetylcholine, histamine and serotonin at 7 x 10-10 g/ml, 1 x 10-7 g/ml and 1 x 10-7 g/ml respectively. The methanol leaf extract of Boscia salicifolia was found to be relatively safe and possess significant anti-diarrhoeal activity, and this justifies the use of this plant in the treatment of diarrhoea in the traditional settings.